Pressure-dependent synthesis of high-quality few-layer graphene by plasma-enhanced arc discharge and their thermal stability - Kumar R.; Singh R.K.; Dubey P.K.; Kumar P.; Tiwari R.S.; Oh I.-K. (My University, 2025)
In this article, a simple and cost-effective method to produce high-quality few-layer graphene (FLG) sheets (∼4 layers) have been achieved by the direct current arc discharge under argon atmosphere, using pure graphite rods as the electrodes. Ar was used as a buffer gas with pure graphite rods as anode and cathode electrodes. We explored the suitable conditions for producing FLG by changing the Ar gas pressure inside the arcing chamber. This method has several advantages over the previous methods to produce graphene for research applications. No toxic and hazardous intercalant was used for producing FLG in this process. The optimum Ar pressure was 500 Torr, for producing minimum number of FLG and this also shows the good thermal stability. The FLG product so obtained has been characterized by X-ray diffraction, scanning and electron microscopy, Raman and Fourier transform infrared spectroscopy. Thermal stabilities of FLG were determined by thermal gravimetric analysis. © 2013 Springer Science+Business Media.